Augmented Reality Untuk Media Promosi Hasil Penelitian - Andrian Wikayanto (Ikatan Ahli Informatika Indonesia (IAII), 2020)
Science & Technopark (STP) was built to accelerate the process of transfer technology of research findings that have been discovered by LIPI. The research findings not only in the form of patents or products but also in the form of tools and buildings. To facilitate the understanding of stakeholders in the research findings an innovative media for the promotion of LIPI research findings was made using Augmented Reality (AR) media. This study uses a linear strategy method that combines text, posters, and videos into AR media. The AR application was tested on 25 LIPI stakeholders by distributing questionnaires using a Likert measurement scale. The results obtained are that AR not only effective in promoting commercial products but also very effective in promoting research products that have been found by LIPI at STP and making promotional activities more interesting and interactive.